2020
DOI: 10.3390/ijms21082974
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of CDK7 Reverses Endocrine Therapy Resistance in Breast Cancer

Abstract: Cyclin-dependent kinase (CDK)-7 inhibitors are emerging as promising drugs for the treatment of different types of cancer that show chemotherapy resistance. Evaluation of the effects of CDK7 inhibitor, THZ1, alone and combined with tamoxifen is of paramount importance. Thus, in the current work, we assessed the effects of THZ1 and/or tamoxifen in two estrogen receptor-positive (ER+) breast cancer cell lines (MCF7) and its tamoxifen resistant counterpart (LCC2) in vitro and in xenograft mouse models of breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Finally, we measured the levels of several drug resistance-, tumorigenesis-, and mitotic-related proteins after rescuing hnRNPU-WT or hnRNPU-4KR ( Figure 6 i and Supplementary Figure S5d ). We showed that the rescue of hnRNPU-WT increases the level of drug resistance- or tumorigenesis-related proteins, such as CDK7 [ 44 , 45 ] or FoxM1 [ 46 ] ( Figure 6 i). Thus, the modulation of the CDC20–hnRNPU axis could improve the chromatin condensation in TNBC, which in turn resensitizes cellular drug response.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we measured the levels of several drug resistance-, tumorigenesis-, and mitotic-related proteins after rescuing hnRNPU-WT or hnRNPU-4KR ( Figure 6 i and Supplementary Figure S5d ). We showed that the rescue of hnRNPU-WT increases the level of drug resistance- or tumorigenesis-related proteins, such as CDK7 [ 44 , 45 ] or FoxM1 [ 46 ] ( Figure 6 i). Thus, the modulation of the CDC20–hnRNPU axis could improve the chromatin condensation in TNBC, which in turn resensitizes cellular drug response.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore attempted to target another cyclin-dependent kinase, CDK7, which is also involved in regulating the cell cycle [ 43 , 56 ]. CDK7 has been identified as a suitable target in drug-resistant BCs and effectively inhibits proliferation of TNBC cells in vitro [ 41 , 57 , 58 ]. Moreover, its specific targeting of tumour cells in vivo with no adverse effects on liver and kidney function were associated with the CDK7i [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…66 Cyclin-dependent kinase 7 (CDK7) inhibitors are emerging as promising BC drugs, being effective for HR+ BC in vitro and in vivo. 67,68 A Phase I trial (NCT03363893) of patients pretreated with CDK4/6 inhibitors is ongoing.…”
Section: Other Targetsmentioning
confidence: 99%